Sowing Sustainable Agriculture: Investigating "Sustainability" in the Academic Discourse on Precision Agriculture - Orzel, Emma Catherine (Université d'Ottawa / University of Ottawa, 2024)
The academic literature suggests that precision agriculture (PA) is revolutionizing the agricultural sector, with claims that it can enhance sustainability through technological advancements such as tractors with automated guidance, sensor suites, satellites, and drones. The literature on PA widely asserts PA has sustainability benefits claiming that these emerging agricultural technologies will address food system challenges. These challenges include improving the state of food security in the face of a growing global population and the ongoing threats of climate change and environmental degradation caused by agriculture by enhancing agricultural efficiency, productivity, and profits for farmers. Despite this pervasive notion of an inherent link between PA and sustainability, questions persist regarding the substantiation of these "sustainability" benefits, particularly in the promotion of these technologies. To investigate this link between PA and sustainability, this thesis considers the following research questions: What are the key factors and influences that have contributed to the enduring connection between PA and sustainability within the academic literature and how is the concept of sustainability conceptualized and operationalized within the academic discourse on PA? Employing an inductive constructivist perspective, this research examines academic literature collected through systematic literature review and interview transcripts from semi-structured interviews with key informants from academia, to explore the dominant models of sustainability present in the literature and the factors that have contributed to the formation of this inherent link. Drawing on this constructivist perspective, the research demonstrates that sustainability is not an inherent aspect of PA but rather a construct shaped by the various actors responsible for the promotion of PA. This implies that those actively advocating for or endorsing PA, construct the understanding and portrayal of sustainability in relation to PA, leading to a convergence of sustainability conceptualizations reflective of existing productivist paradigms in agriculture. Considering these findings, this thesis contributes to the greater literature which asserts that PA, although full of promise, may reinforce the issues created by contemporary agriculture.
Keywords: Precision Agriculture; Sustainability; Productivism